2019
DOI: 10.1200/jop.19.00184
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of Patients With Cancer on Accessing Cannabis Products in a State With Restrictive Medical Marijuana Laws: A Survey Study

Abstract: PURPOSE: Several states, particularly in the Southeast, have restrictive medical marijuana laws that permit qualified patients to use specific cannabis products. The majority of these states, however, do not provide avenues for accessing cannabis products such as in-state dispensaries. METHODS: We conducted a survey of patients registered for medical marijuana (low tetrahydrocannabinol [THC] oil cards) in an ambulatory palliative care practice in Georgia (one of the states with restrictive medical marijuana la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
1
14
0
2
Order By: Relevance
“…264 Within the state of Georgia, Singh reported that 32% of patients accessed their cannabis products from a private supplier and 57% shipped it from out of state, whilst 10% reported using a medical cannabis dispensary. 262 As with my study, cost and access regarding cannabis-related products rated highly as a concern in multiple studies, regardless of diagnosis. [97][98][99][100]262 Whilst a recent study of NZ medicinal cannabis users, regardless of diagnosis, indicated that smoking was the primary mode of administration, 99 this study indicated that oncology patients were just as likely to use oils and edibles.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…264 Within the state of Georgia, Singh reported that 32% of patients accessed their cannabis products from a private supplier and 57% shipped it from out of state, whilst 10% reported using a medical cannabis dispensary. 262 As with my study, cost and access regarding cannabis-related products rated highly as a concern in multiple studies, regardless of diagnosis. [97][98][99][100]262 Whilst a recent study of NZ medicinal cannabis users, regardless of diagnosis, indicated that smoking was the primary mode of administration, 99 this study indicated that oncology patients were just as likely to use oils and edibles.…”
Section: Discussionmentioning
confidence: 64%
“…262 As with my study, cost and access regarding cannabis-related products rated highly as a concern in multiple studies, regardless of diagnosis. [97][98][99][100]262 Whilst a recent study of NZ medicinal cannabis users, regardless of diagnosis, indicated that smoking was the primary mode of administration, 99 this study indicated that oncology patients were just as likely to use oils and edibles. This is in keeping with an Australian study by Luckett et al, where in oncology patients who were surveyed about cannabis and possible participation in a clinical trial for anorexia and appetite loss indicated a preference for oral administration of medicinal cannabis products (71%).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations